2011
DOI: 10.2119/molmed.2011.00178
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of SH2 Domain-Containing Inositol-5′-Phosphatase 1 (SHIP1) and SHIP2 Inhibition in Cancer

Abstract: Many tumors present with increased activation of the phosphatidylinositol 3-kinase (PI3K)-PtdIns(3,4,5)P 3 -protein kinase B (PKB/Akt) signaling pathway. It has long been thought that the lipid phosphatases SH2 domain-containing inositol-5′-phosphatase 1 (SHIP1) and SHIP2 act as tumor suppressors by counteracting with the survival signal induced by this pathway through hydrolysis or PtdIns(3,4,5)P 3 to PtdIns(3,4)P 2 . However, a growing body of evidence suggests that PtdInd(3,4)P 2 is capable of, and essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
116
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(126 citation statements)
references
References 42 publications
10
116
0
Order By: Relevance
“…SHIP1 inhibitor (3AC) treatment blocked PtdIns(3,4,5)P 3 hydrolysis by SHIP1 in vitro, but reduced human MM cell growth and viability and decreased IGF-1-induced phosphorylation of Akt [69]; contrasting with observations in murine Ship1-null cell lines. In addition, treatment with pan-SHIP1/2 inhibitors (1PIE, 2PIQ and 6PTQ) in MDA-MB-231 and MCF-7 human breast cancer cell lines prevented SHIP2-mediated PtdIns(3,4,5)P 3 degradation, decreased IGF-1-stimulated Akt phosphorylation and induced cell cycle arrest and apoptosis in a similar manner to SHIP1 inhibition in MM cells [58]. SHIP1/2 inhibitor-induced decreases in cell viability were rescued by exogenous addition of PtdIns(3,4)P 2 , suggesting that the production of PtdIns(3,4)P 2 by SHIP1 and SHIP2 and not the loss of PtdIns(3,4,5)P 3 , maintains cell viability (although exogenous PtdIns(3,4,5)P 3 was not added in these studies) [58,69].…”
Section: Development Of Agonists and Inhibitors To Ship1 And Ship2mentioning
confidence: 86%
See 3 more Smart Citations
“…SHIP1 inhibitor (3AC) treatment blocked PtdIns(3,4,5)P 3 hydrolysis by SHIP1 in vitro, but reduced human MM cell growth and viability and decreased IGF-1-induced phosphorylation of Akt [69]; contrasting with observations in murine Ship1-null cell lines. In addition, treatment with pan-SHIP1/2 inhibitors (1PIE, 2PIQ and 6PTQ) in MDA-MB-231 and MCF-7 human breast cancer cell lines prevented SHIP2-mediated PtdIns(3,4,5)P 3 degradation, decreased IGF-1-stimulated Akt phosphorylation and induced cell cycle arrest and apoptosis in a similar manner to SHIP1 inhibition in MM cells [58]. SHIP1/2 inhibitor-induced decreases in cell viability were rescued by exogenous addition of PtdIns(3,4)P 2 , suggesting that the production of PtdIns(3,4)P 2 by SHIP1 and SHIP2 and not the loss of PtdIns(3,4,5)P 3 , maintains cell viability (although exogenous PtdIns(3,4,5)P 3 was not added in these studies) [58,69].…”
Section: Development Of Agonists and Inhibitors To Ship1 And Ship2mentioning
confidence: 86%
“…In addition, treatment with pan-SHIP1/2 inhibitors (1PIE, 2PIQ and 6PTQ) in MDA-MB-231 and MCF-7 human breast cancer cell lines prevented SHIP2-mediated PtdIns(3,4,5)P 3 degradation, decreased IGF-1-stimulated Akt phosphorylation and induced cell cycle arrest and apoptosis in a similar manner to SHIP1 inhibition in MM cells [58]. SHIP1/2 inhibitor-induced decreases in cell viability were rescued by exogenous addition of PtdIns(3,4)P 2 , suggesting that the production of PtdIns(3,4)P 2 by SHIP1 and SHIP2 and not the loss of PtdIns(3,4,5)P 3 , maintains cell viability (although exogenous PtdIns(3,4,5)P 3 was not added in these studies) [58,69]. Collectively, small molecule-mediated SHIP1 activation and SHIP1/2 inhibition in cancer cell lines both paradoxically reduce Akt activation, suggesting context-and cell typedependent regulation of PtdIns(3,4)P 2 and PtdIns(3,4,5)P 3 and subsequent Akt activation.…”
Section: Development Of Agonists and Inhibitors To Ship1 And Ship2mentioning
confidence: 86%
See 2 more Smart Citations
“…Fuhler et al have demonstrated a role of phosphatases in myeloma survival and drug resistance, suggesting that they too may be critical mediators of the survival signaling induced under co-stimulatory conditions. 39,40 …”
Section: Discussionmentioning
confidence: 99%